Enantioselective Esterification Of (±)-Menthol With Butyric Anhydride By Chemically Modified Candida Rugosa Lipase - Jasmani, Halila (2003)
Commercial lipase from Candida rugosa was chemically modified with the aim to improve its catalytic properties in organic solvents. The chemical modifiers, aldehydes and monomethoxy polyethylene glycols, were covalently linked to the lysine residues at the surface of the enzyme. Enzymatic enantioselective esterification of racemic menthol in organic solvents using butyric anhydride as acylating agent was performed with the chemically modified lipases. Different degrees of modification, organic solvents, reaction temperatures and water activity were examined for the influence on the percent yield and enantioselective formation of (-)-menthyl butyrate. The percent yield increased as the degree of modification increased but decreased slightly for the highest degree of modification. Organic solvents with log P values above 2.5 gave higher yield, however high enantioselectivity was obtained in all the organic solvents tested. The enantioselectivity towards (-)-menthol decreased considerably as the reaction temperature was increased. Enzyme derivatives exhibited better activity and enantioselectivity at high aw. The alkylated lipases showed higher thermal, solvent